Retrofit of multiproduct batch plants through generalized disjunctive programming - Montagna, Jorge Marcelo (2003)
The retrofit problem for multiproduct batch plants deals with the modification of the original structure of the plant to meet new production conditions such as the introduction of new products, a new supply pattern, etc. For this problem, a disjunctive model is presented, which takes into consideration every usual alternative about the configuration of units and storage tanks. A disjunction is generated for that purpose. The selection of one of those alternatives sets up all the corresponding constraints, which are: operation time, unit size and cost, etc. Finally, the performance of this approach is analyzed through the resolution of a set of examples.